A Review on Multimodal Medical Image Fusion (Journal of Pharmaceutical Negative Results, 2023)
Multimodal medical image fusion is a current technique applied in applications related to medical field to combine images from the same modality or different modalities to improve the visual content of the image to perform further operations like image segmentation. Biomedical research and medical image analysis highly demand medical image fusion to perform higher level of medical analysis. Multimodal medical fusion assists medical practitioners to visualize the internal organs and tissues. Multimodal medical fusion of brain image helps to medical practitioners to simultaneously visualize hard portion like skull and soft portions like tissue.